AN ANALYSIS OF CULTURAL CONTENT IN ENGLISH TEXTBOOKS FOR VOCATIONAL HIGH SCHOOL - Neviana Wahyuni; Sudarsono Sudarsono; Clarry Sada (ICoTE Proceedings, 2018)
The 2003 Act of the Republic of Indonesia on the National Education System suggests the teachers' responsibility for maintaining the Indonesian national culture, rooted in the values of religion and local wisdom. As textbooks are generally considered to be the major source of the teaching materials, they have an important role in integrating cultures or cultural elements in the teaching and learning process. This study investigated cultural content in two English textbooks. This study aimed to find out the percentage of local culture integration and target culture integration in two English textbooks “Bahasa Inggris” by Ministry of Education and “Forward” by Erlangga, especially about how cultures represented in pictures in both of books. This research design was a content analysis with 76 paragraph and 105 pictures as the study data. The procedure of analyzing the data started by classifying the data into local or target culture division, then it was analyzed based on Byram’s cultural content checklist (1993) while the pictures were simply classified into local culture or target culture. The result of the analysis was made in the form of a percentage, it concluded that from two-course books analyzed in this study, Bahasa Inggris are now aware in promoting local culture and Forward still have lack of local cultural content inserted in the books.